Carbon-Coated Magnetic Nanoparticle Dedicated to MRI/Photoacoustic Imaging of Tumor in Living Mice - Li, Yujing; Ye, Fei; Zhang, Shanxiang; Ni, Wenjun; Wen, Liewei; Qin, Huan (Frontiers in Bioengineering and Biotechnology, 2021)
Multimodality imaging can reveal complementary anatomic and functional information as they exploit different contrast mechanisms, which has broad clinical applications and promises to improve the accuracy of tumor diagnosis. Exploiting multimodal contrast agents is of great significance to this purpose. In the present work, we develop a novel cobalt core/carbon shell-based nanoparticles (Cobalt@ carbon NPs) with both magnetization and light absorption properties for dual-modality magnetic resonance imaging (MRI) and photoacoustic imaging (PAI). The nanoparticle consists of ferromagnetic cobalt particles coated with carbon for biocompatibility and optical absorption. The prepared Cobalt@ carbon NPs are characterized by transmission electron microscopy (TEM), visible-near infrared spectra, Raman spectrum and X-Ray powder diffraction for structural analysis. Experiments verify that Cobalt@ carbon NPs has been successfully constructed and the designed Cobalt@ carbon NPs can be detected by both MRI and PAI in vitro and in vivo. Importantly, intravenous injection of Cobalt@ carbon NPs into glioblastoma-bearing mice led to Cobalt@ carbon NPs accumulation and retention by the tumors. Using such a multifunctional probe, MRI can screen rapidly to identify potential lesion locations, while PAI can provide high-resolution morphological structure and quantitative information of the tumor. The Cobalt@ carbon NPs are likely to become a promising candidate for dual-modality MRI/PAI of tumor.